Julio Calvo Pérez y Carlos Hernández Sacristán (eds.), Perceptual and topological criteria in linguistics description. University of Minnesota, Minneapolis; Universitat de València, 1988; 159 pp. (LynX. A monographic series in linguistics and world percpetion, 1). - García Fajardo, Josefina (El Colegio de México, 1990)
Se reseñó el libro: Perceptual and topological criteria in linguistics description.